Tribological Behavior and Cold-Rolling Lubrication Performance of Water-Based Nanolubricants with Varying Concentrations of Nano-TiO2 Additives - Linan Ma; Luhu Ma; Junjie Lian; Chen Wang; Xiaoguang Ma; Jingwei Zhao (Lubricants)
This study aimed to investigate the effect of water-based nanolubricants containing varying concentrations (1.0–9.0 wt.%) of TiO2 nanoparticles on the friction and wear of titanium foil surfaces. Water-based nanolubricants containing TiO2 nanoparticles of varying concentrations were prepared and applied in friction and wear experiments and micro-rolling experiments to evaluate their performance regarding friction and wear properties. The findings indicated that the best results were achieved with a 3.0 wt.% TiO2 nano-additive lubricant that significantly improved the tribological properties, with reductions in the COF and wear of 82.9% and 42.7%, respectively, compared to the dry conditions without any lubricant. In addition, nanolubricants contribute to a reduction in rolling forces and an improvement in the surface quality of titanium foils after rolling. In conclusion, nanolubricants exhibit superior lubricating properties compared to conventional O/W lubricants, which is attributed to the combined effect of the rolling effect, polishing effect, mending effect and tribo-film effect of the nanoparticles.